Nature as a source of joy in wiliam wordsworth's poem I wandered lonely as cloud: - - Mita Yuwana, Valiza Alika; Nasution, Jamaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
William Wordsworth's poem I Wandered Lonely as a Cloud is the subject of this investigation, which examines the portrayal of nature as a source of pleasure. The objective of the research is to ascertain the manner in which nature is depicted in the poem and to elucidate its impact on the speaker's emotional experience. An ecocritical approach was implemented to apply a qualitative descriptive-analytical methodology. The primary data was composed of words, phrases, lines, and stanzas from the poem that depict natural elements and expressions of pleasure. The data were collected using documentation techniques and analyzed using the stages of data reduction, data display, and conclusion drawing. The results show that nature significantly influences the speaker's emotional state. The speaker initially feels isolated and lonely; however, the golden daffodils evoke emotions.